Online Extremism in Russia : Assessing Putin’s Move - Cheang, Chris (2018)
In a calculated move, President Vladimir Putin intervened to lessen the impact of an anti-extremism piece of legislation. He is not getting soft against extremism. The main consideration is his ability to stay popular and remain in power.